Intelligent adaptive environments: proposal for inclusive, interactive design enabling the creation of an interconnected public open space on the Iron Horse trestle interurban-railroad-subway [St. Louis, Missouri] - Anterola, Jeremy K. (Kansas State University, 2009)
Economically insecure times require reduction of energy and land consumption, enhancement of socio-economic and environmental quality of life, and reutilization of neglected existing structures and sites. Traditional planning and design dictates through top-down policy and ordered master planning. In contrast, interactive smart technology simulating human cognitive reactions offers an alternative design framework - an intelligent, adaptive environment – capable of redefining contemporary public open space design. Traversing through the neglected Fifth Ward north of downtown St. Louis, the adaptive reutilization of the abandoned Iron Horse Trestle interurban elevated railroad and subway applies the Sense Respond Adapt Mutate Emerge conceptual framework (the S.R.A.M.E. Strategy) by utilizing existing resources to create an interconnected, emergent open space network. Ten unique sites along the Iron Horse Trestle are initially embedded with sensory devices capable of gathering and synthesizing learned information. The real-time actions translate into physical structural responses. The site specifi c reactions extend outwards as structural adaptations to indeterminate changes from trail users. The evolving structural form connects and mutates the existing structure. Similar to a Choose your own adventure gamebook, the Trestle’s open-ended and reactive programmatic strategies emerge as a series of potential options for future inclusionary, interactive designs. By selectively enhancing, creating, or enabling an open space system reacting to real-time actual user needs over time directly along the Trestle line, the S.R.A.M.E. Strategy offers a potential alternative framework for the indirect revitalization of neglected infrastructural and economic conditions, a residential rejuvenation catalyst, and future socio-economic and ecological sustainable living patterns education tool. The Trestle’s revitalization serves as an education tool critiquing contemporary landscape architecture and general design practice - the static, dictated, and consumptive. Intelligent adaptive environments offer an alternative framework enabling interactive design decision making capabilities to the users as options evolving over time.
Keywords: adaptive environments; redefining public space; emergent technology; enhancing blighted urban areas; infrastructural adaptive reuse; landscape architecture practice; Artificial Intelligence (0800); Landscape Architecture (0390); Urban and Regional Planning (0999)